South-South technology transfer of low-carbon innovation: large Chinese hydropower dams in Cambodia - Urban, Frauke; Siciliano, Giuseppina; Sour, Kim; Lonn, Pich Dara; Tan-Mullins, May; Mang, Grace (Wiley, 2015)
Large dams have been controversially debated for decades due to their large‐scale and often irreversible social and environmental impacts. In the pursuit of low‐carbon energy and climate change mitigation, hydropower is experiencing a new renaissance. At the forefront of this renaissance are Chinese actors as the world's largest hydropower dam‐builders. This paper aims to discuss the role of South–South technology transfer of low‐carbon energy innovation and its opportunities and barriers by using a case study of the first large Chinese‐funded and Chinese‐built dam in Cambodia. Using the Kamchay Dam as an example, the paper finds that technology transfer can only be fully successful when host governments and organizations have the capacity to absorb new technologies. The paper also finds that technology transfer in the dam sector needs to go beyond hardware and focus more on the transfer of expertise, skills and knowledge to enable long‐term sustainable development.